Antioxidant Effect of Propofol in Gliomas and Its Association With Divalent Metal Transporter 1 - Yang, Chenyi; Xia, Zhengyuan; Li, Tang; Chen, Yimeng; Zhao, Mingshu; Sun, Yi; Ma, Ji; Wu, Yi; Wang, Xinyue; Wang, Peng; Wang, Haiyun (Frontiers in Oncology, 2020)
Background: Oxidative stress enhances tumor invasion and metastasis in brain cancer. The activation of divalent metal transporter 1 (DMT1), which is regulated by glutamate receptors, can result in the increase of oxidative stress and risk of cancer development. Propofol, an anesthetic with antioxidant capacity, has been shown to decrease oxidative stress in several different types of cancer. However, the underlying mechanism remains unclear. Therefore, the present study aimed to elucidate the mechanism underlying the suppression of oxidative stress in glioma cells by propofol. It was hypothesized that propofol may inhibit oxidative stress in gliomas via suppressing Ca2+-permeable α-amino-3-hydroxyl-5-methylisoxazole-4-propionic acid (AMPA) receptor (CPAR)-DMT1 signaling. Methods: Male Wistar rats with C6 gliomas, which were established by intracranial injection of C6 glioma cells, were either treated with propofol or not for 6 h before being sacrificed. The levels of AMPA receptor subunit GluR2 and DMT1 protein expression were assessed using western blotting. The association between CPARs and DMT1 was confirmed in vitro using the AMPA receptor activator (R, S)-AMPA. Glutathione and reactive oxygen species assay kits were used to evaluate tumor oxidative stress. The effect of propofol on glioma proliferation was evaluated by determining tumor weight, cell cycles and a growth curve. Results: Propofol infusion at either 20 or 40 mg/kg-1/h-1 increased GluR2 levels and downregulated DMT1 expression as well as glutathione content markedly in the periphery compared with that in the glioma core. The in vitro results revealed that (R, S)-AMPA increased DMT1 expression and reactive oxygen species levels, which were partly reversed by propofol treatment. Conclusion: Propofol regulated DMT1 expression by modulating CPARs, resulting in the inhibition of tumor oxidative stress and glioma growth. The present study provides evidence for optimizing the selection of anesthetic drugs in perioperative management and prognosis of patients with glioma.